The importance of environmental law - Karski, Leszek (Studia Ecologiae et Bioethicae, 2011)
This article addresses the concept of environmental law. The paper begins with a general background on the justification for the study of environmental law. The second section focuses on the nature of law. In the next section the author analyses legal definitions of environmental protection and environment. As the analysis shows that environmental legislation plays a crucial role, the final section discusses its location in the Polish legal system. This study highlights that environmental law should be treated as a branch of law.